Overcoming therapeutic inertia as the achilles heel for improving suboptimal diabetes care: An integrative review - Chew, Boon-How; Mohd-Yusof, Barakatun-Nisak; Lai, Pauline Siew Mei; Khunti, Kamlesh (Korean Endocrine Society, 2023)
The ultimate purpose of diabetes care is achieving the outcomes that patients regard as important throughout the life course. Despite advances in pharmaceuticals, nutraceuticals, psychoeducational programs, information technologies, and digital health, the levels of treatment target achievement in people with diabetes mellitus (DM) have remained suboptimal. This clinical care of people with DM is highly challenging, complex, costly, and confounded for patients, physicians, and healthcare systems. One key underlying problem is clinical inertia in general and therapeutic inertia (TI) in particular. TI refers to healthcare providers’ failure to modify therapy appropriately when treatment goals are not met. TI therefore relates to the prescribing decisions made by healthcare professionals, such as doctors, nurses, and pharmacists. The known causes of TI include factors at the level of the physician (50%), patient (30%), and health system (20%). Although TI is often multifactorial, the literature suggests that 28% of strategies are targeted at multiple levels of causes, 38% at the patient level, 26% at the healthcare professional level, and only 8% at the healthcare system level. The most effective interventions against TI are shorter intervals until revisit appointments and empowering nurses, diabetes educators, and pharmacists to review treatments and modify prescriptions.